Coordinated changes in cellular behavior ensure the lifelong maintenance of the hippocampal stem cell population - Harris, Lachlan; Rigo, Piero; Stiehl, Thomas; Gaber, Zachary B.; Austin, Sophie H. L.; Masdeu, Maria del Mar; Edwards, Amelia; Urbán, Noelia; Marciniak-Czochra, Anna; Guillemot, François (Cell stem cell, 2021)
Neural stem cell numbers fall rapidly in the hippocampus of juvenile mice but stabilize during adulthood, ensuring lifelong hippocampal neurogenesis. We show that this stabilization of stem cell numbers in young adults is the result of coordinated changes in stem cell behavior. Although proliferating neural stem cells in juveniles differentiate rapidly, they increasingly return to a resting state of shallow quiescence and progress through additional self-renewing divisions in adulthood. Single-cell transcriptomics, modeling, and label retention analyses indicate that resting cells have a higher activation rate and greater contribution to neurogenesis than dormant cells, which have not left quiescence. These changes in stem cell behavior result from a progressive reduction in expression of the pro-activation protein ASCL1 because of increased post-translational degradation. These cellular mechanisms help reconcile current contradictory models of hippocampal neural stem cell (NSC) dynamics and may contribute to the different rates of decline of hippocampal neurogenesis in mammalian species, including humans.